Penyimpangan Dalam Praktik Covernote Notaris Pada Transaksi Kredit Bank: Analisis Tanggung Jawab Dan Implikasi Hukumnya - Endhita Shafa Anargya; Kartika Putri Ramadhani; Dathitta Kuhna (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2026)
Through credit disbursement based on prudential principles, banking plays a vital role in the national economy. Often, the credit drawdown process requires administrative support from a notary, who issues a covernote as a temporary statement while collateral documents are being processed. However, the lack of clear regulations regarding the legal status of covernotes leads to legal uncertainty, irregularities, and risks for banks. The objective of this research is to examine the notary's liability in issuing covernotes as a basis for credit disbursement and as a form of legal protection for banking creditors. This study employs a normative juridical method, utilizing statutory, conceptual, and case approaches. The findings indicate that while a covernote is not an original deed, its issuance remains the professional responsibility of the notary. Conversely, legal protection for banks can only be achieved through the application of prudential principles, the completeness of credit agreements, and recourse (regress) against the notary if a violation is proven. This research suggests the need for clear regulations regarding the utilization of covernotes in the banking industry.